Evaluation Of Caregivers’ Knowledge, Attitude, And Practice On Medication Administration Process And Emotional Status In Long-Term Care Facilities In Penang, Selangor, And Kuala Lumpur, Malaysia - Leow, May Yen (2017)
The world’s population is ageing; virtually every country in the world is experiencing growth in the number and proportion of older persons in their population. Ageing is the increasing share of older persons in the population and is poised to become one of the most significant social transformations of the twentyfirst century. Hence, the demand for long-term care facilities (LTCs) will be increased accordingly. 26 LTCs was surveyed to evaluate the quality of the institution's service on medication administration (MA) process. The aim of this research was to assess the level of knowledge, attitude, and practice (KAP) on MA process, and their associated predictors such as emotional, and education level among respondents at LTCs.